PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL (PUTUSAN NO. 27/PDT.SUS-PHI/2022/PN.MDN): Settlement Of Industrial Relations Disputes (Ruling No. 27/Pdt.Sus-Phi/2022/Pn.Mdn) - Muhammad Faris Hilmy; Yogo Pamungkas (AMICUS CURIAE, 2025)
Disputes or conflicts of interest between employers and workers/laborers often occur and are regulated in Law Number 2 of 2004 concerning Settlement of Industrial Relations Disputes. However, it is also different from the District Court decision Number 27/Pdt.Sus-PHI/2022/Pn.Mdn where an Industrial Relations Dispute occurred, namely the termination of employment relations but the Law was not implemented properly. The problem with this decision is firstly whether the termination of Ibrahim Simanjuntak's employment by PT. Is Tor Ganda in accordance with Law Number 13 of 2003 concerning Employment? and Second, whether the settlement of industrial relations between Ibrahim Simanjuntak and PT. Is Tor Ganda in accordance with Law Number 2 of 2004 concerning PPHI? This research uses normative law using secondary data made from primary, secondary and tertiary law, data processing techniques are carried out qualitatively by drawing conclusions using deductive methods. The conclusion of this research is that the termination of employment relations which turned out to be Ibrahim Simanjuntak's resignation or resignation was in accordance with Article 162 paragraph (4) of Law Number 13 of 2003 and the industrial relations settlement was invalid because it contained formal defects so that the PHI Panel of Judges decided It was wrong to hand down a decision which should be null and void by law.